Evaluation of the Korean Middle School English Textbook: Listening Skill - Hanbi Jeong (Kata Kita: Journal of Language, Literature, and Teaching, 2019)
This study is done to find out how listening skill is presented in Middle School English 1 textbook published in 2018. In order to answer the research question, the writer used the criteria proposed by Cunningsworth (1995). This is a qualitative research in which the writer evaluated and analyzed by herself. The findings of this study show that listening skill in Middle School English 1 met the criteria proposed by Cunningsworth (1995). Keywords: textbook, textbook evaluation, curriculum